Electrochemical reactors for PGM recovery - Ferreira, Bronwynne Kim (My University, 2006)
The employment of an electrochemical process is an attractive alternative for the treatment of effluents. When dealing with solutions of low metal ion concentrations mass transport limitations are significant and large electrode surfaces are required. The use of a reactor containing a three-dimensional electrode is preferable as the surface area per unit volume is orders of magnitude greater than that of the familiar plate type reactor. A benchscale electrochemical reactor was designed and constructed to incorporate a cylindrical packed bed cathode. The flow of electrolyte is perpendicular to the direction of the flow of the current and the system is operated galvanostatically in a batch recirculation mode. The industrial stream selected for examination contains palladium and copper ions and a small concentration of platinum in a chloride medium containing ammines. The evolution of chlorine gas at the anode by the oxidation of the chloride ions is prevented by the inclusion of a cation exchange membrane and a separate anolyte, namely sulphuric acid, is introduced to the outer anodic chamber. Tests were conducted on both synthetic and industrial solutions and a simplified model which was derived was used to estimate the mass transfer coefficients. The concentrations of the palladium, copper and platinum in the plant effluent were approximately 150, 200 and 10 ppm respectively. The results show that the metal ions can be rapidly reduced to well below 1 ppm in each case. The separation of the palladium and copper ions is shown to occur to a limited degree during electrodeposition, with the extent of separation increasing for lower current densities. Enhanced separation may be possible during the removal of the deposited metals from the cathode either by anodic stripping or chemical treatment. A further method for the recovery of the metals is the combustion of the graphite particles. The high value of palladium, coupled with the significant recoveries shown to be achievable, suggest economic viability in addition to the environmental benefits.
Master of Science in Engineering - Engineering
Keywords: recovery; pgm; reactors; electrochemical